PENGARUH PENGGUNAAN MEDIA POSTER TERHADAP HASIL BELAJAR TEMATIK TEMA 2 SUBTEMA 2 SISWA KELAS IV SD NEGERI 102010 LIBERIA - Rahman Sihotang; Regina Fredika Sipayung (LP3M KH Yazid Karimullah Institute, 2024)
This study aims to determine whether or not there is an effect of poster media on student learning outcomes in thematic learning theme 2 subtheme 2 Class IV of 102010 Liberia State Elementary School. This study used an experimental method with a True Experimental design with a pretest-posttest control group design type conducted at IV State Elementary School 102010 Liberia in class IV students with a population of 44 students and a sample of 22 students. The research data collection technique used a 2-time test, namely pretest-posttest. Data analysis techniques used in this study are Descriptive Statistical Analysis and Inferential Statistical Analysis. Testing the research hypothesis using the t-test pretest-posttest control group design, and to see the effectiveness of the influence of poster media is done using the Normality Test. The final results of the study showed that there was an effect of poster media on the learning outcomes of grade IV students, with the results of hypothesis test analysis showing t-count (9.550) while the t-table value (1.721), because t-count> t-table, it is proven that there is an effect of poster media on the learning outcomes of grade IV students.